2019
DOI: 10.1007/s00706-019-02391-w
|View full text |Cite
|
Sign up to set email alerts
|

(Thio)urea containing quaternary ammonium salts for the CO2-fixation with epoxides

Abstract: A detailed screening of differently substituted chiral and achiral (thio)urea-containing quaternary ammonium salts revealed their potential as catalysts for the CO 2-fixation with epoxides to obtain cyclic carbonates in high yields under operationally simple atmospheric pressure conditions. Additional DFT calculations substantiate a mechanism involving an initial addition of the nucleophilic iodide counter anion of the ammonium salt to the H-bonding activated epoxide, followed by stepwise CO 2-fixation and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The catalytic activity of the N‐DFNS‐700/TBAI system was further compared with recently reported catalysts and it was observed that the N‐DFNS showed comparable activity at mild reaction conditions (Table 2). [16–31] …”
Section: Resultsmentioning
confidence: 99%
“…The catalytic activity of the N‐DFNS‐700/TBAI system was further compared with recently reported catalysts and it was observed that the N‐DFNS showed comparable activity at mild reaction conditions (Table 2). [16–31] …”
Section: Resultsmentioning
confidence: 99%
“…During the whole process, thiourea not only activated hydrogen bonds but also promoted the conversion of carbon dioxide, playing a synergistic role with the adjacent quaternary ammonium salt components to ensure the coupling reaction proceed smoothly. It should be mentioned that other possible mechanisms like thiourea catalyst as a nucleophile also have been proposed …”
Section: Resultsmentioning
confidence: 99%
“…Diallyl‐dibutyl‐ammonium bromide ( N m1 ), triallyl‐butyl‐ammonium bromide ( N m2 ), tetraallyl‐ammonium bromide ( N m3 ), and N, N′‐diallylthiourea ( L m1 ) were prepared according to the literature and more detail were provided in Figure S1. Pentaerythritol tetrakis (3‐mercaptopropionate) ( C m3 ), diphenyl (2,4,6‐trimethylbenzoyl) phosphine oxide (TPO) and all epoxides were purchased from Sun Chemical Technology Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…32 The urea moiety on the ammonium bromide catalyst functions as a hydrogen-bonding donor to activate epoxide substrates. 33,34 An optimized bifunctional ammonium bromide catalyst could efficiently promote the reaction of glycidyl ethers and aryl isocyanates to provide corresponding 2-oxazolidinone products 1 in good to high yields.…”
Section: Bifunctional Organocatalystsmentioning
confidence: 99%